Sibisa Cultural Art Center and Gallery, Toba Samosir - Hajar Suwantoro; Yesica Munthe (Talenta Publisher, 2018)
Lake Toba is one of the areas in Indonesia that has an attractive culture and tourism sector. Therefore the government targets lake Toba performance, as one of the destinations that will be prioritized especially, foreign tourists. But the facilities and infrastructure for the tourists to enjoy the diversity of local culture is still below standard. Therefore, the Sibisa cultural arts center as well as close to Sibisa airport is something that is expected to meet the needs of tourists who come to visit and enjoy the local culture and also accommodate artisans of local art workers culture.